Actualization of Hasan Al-Bana Holistic Integral Education in Integrated Islamic School - Syafitri, Lely Nur Hidayah (Proceeding International Conference on Religion, Science and Education, 2022)
This study aims to analyze the idea of Hasan Al-Bana's Integral holistic education and its correlation with educational practices at the Integrated Islamic School which indicates an ideological relationship between Hasan Albana's thought and its application in an integrated Islamic school. Both seek to integrate the dichotomous education system between religious education and general education by returning to pure teaching sources based on the Qur'an and Sunnah, which universally and integratedly develop all human potential. This study used library research and qualitative methods through interviews. From the results of the analysis, it is known that the purpose of Islamic education is to construct the quality of human resources, namely students, and the education system must be based on a strong foundation that is able to give birth to a young generation with Islamic immunity, moral wisdom, and mastery of comprehensive knowledge, which will be reflected in various aspects of life. Hasan Albana established four aspects to realize his goals, first, the aspect of intelligence or intellectual education. Second, aspects of moral education, Third, aspects of physical and spiritual education. Fourth, the aspect of social education. All these materials can be obtained through the science of religion, exact sciences, social sciences, and their branches. In addition, the results of observations show that educational practices in integrated Islamic schools have ideological and practical relevance to the thought of Hasan Albana. In the ideological area, Hasan Albana's thoughts became the ideological basis of education in integrated Islamic schools. And in its application, Hasan Albana's thinking is implemented in educational practice as a special curriculum. In particular, the integrated Islamic school was inspired by the Tarbiyah Ikhwanul Muslimin movement founded by Hasan Albana in Egypt.